Produktivitas Primer Perifiton di Sungai Naborsahan Sumatera Utara - Betzy Victor Telaumbanua; Ternala Alexander Barus; Ani Suryanti (AQUACOASTMARINE, 2013)
The aimed of this research is to know diversity and abundance of periphytonand to know the primary productivity of periphyton in the Naborsahan River.Water quality parameters measured were temperature, current, dissolved oxygen(DO), nitrate, orthophosphate and abundance of periphyton. The observationswere made four times in two the research station. Sample taking carried is threetime repetition on each station. Based on the result obtained the periphytondiversity ranged from 2.903 to 2.971, the abundance of periphyton ranged from79.02 to 329.76 ind/cm2 and periphyton primary productivity value ranged from57.140 to 571.405 mgC/m3/day.Keywords: periphyton, primary productivity, Naborsahan River